The influence of coach leadership behavior on athletes` prosocial behavior in sports: the mediating effect of goal orientation and moral disengagement in sports - Bu, X.; Huang, Z.; Zheng, S.; Zhang, Y.; Ma, S.; Kang, Y. (PLOS ONE, 2026)
To investigate the impact of coach leadership behavior on athletes` prosocial behavior in sports, as well as the mediating role of goal orientation and moral disengagement in it, a questionnaire survey was conducted on 1239 athletes. The results showed that democratic leadership behavior has significant positive and negative effects on athletes` prosocial behavior and antisocial behavior in sports, respectively; Authoritarian leadership behavior has significant negative and positive impact on athletes` prosocial behavior and anti social behavior in sports, respectively; Both democratic leadership behavior and authoritarian leadership behavior can have a significant indirect impact on prosocial behavior and antisocial behavior in sports through the mediating effect of goal orientation and moral disengagement. Specific mediating paths include independent mediating paths of self-orientation, task orientation, and moral disengagement in sports, and chain mediating paths of self-orientation and moral disengagement in sports. In the future, coaches can enhance democratic leadership, reduce authoritarian leadership behavior, adjust athletes` goal orientations, and lower moral disengagement levels, thereby suppressing antisocial behavior and promoting prosocial behavior in sports.